O situaciji ali statusu slovenščine na Koroškem - Malle, Avguštin (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2001)
Regarding minority languages in Austria it is not possible to speak about their "normalization" in the sense of linguistic equality. These are mostly standardized and developed literary languages. In the process of promotion ofethnicity, Slovene was a subject of wide political endeavours for its socialstatus. Minority languages in Austria are gradually losing their original basis and their primary passing on is being shifted from family framework to that of educational and school institutions. Languages are primary factors according to which minorities are defined. The attitude of the majority towards minority language reaches from a distinct refusal to support. In Carinthia the presence of Slovene in public segments varies. A decisive factor for the existence and promotion of minority languages is that their speakers have at their disposal as wide a network of factors as possible which provides for their free and functional use.
Keywords: Austria; Avstrija; Koroška; koroški Slovenci; Carinthian Slovenes; narodne manjšine; jezikovne manjšine; dvojezičnost; bilingualism; Slovene; slovenščina; German; nemščina